China’s economic involvement in Mozambique and prospects for development : an analysis of the processes and impacts of major recent investments - Alvarenga Rodrigues, Daniel Guilherme (Stellenbosch : Stellenbosch University, 2008)
Thesis (MA (Political Science. International Studies))--Stellenbosch University, 2008.